PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PERSONEL POLSEK SEDAYU (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
The objectives of this study were to: 1) determine whether there is an effect of transactional and transformational leadership styles on the performance of the Sedayu Police personnel either partially or simultaneously. 2) knowing the most dominant leadership style on the personnel performance of the Sedayu Police. The research approach used in this research is quantitative methods using survey methods with descriptive analysis and multiple linear regression. The results showed that 1) There is a positive and significant influence between leadership style (X1) on the performance of the Sedayu Police personnel (Y). 2) there is a positive and significant influence between the leadership style (X2) and the personnel performance of the Sedayu Police (Y). 3) there is a joint influence of the variable variable transactional leadership style (X1) and transformational leadership style (X2) on the performance of the Sedayu Police personnel (Y). 4) The most dominant variable with the personnel performance of the Sedayu Police (Y) is the transactional leadership style
Keywords: leadership; performance